2019
DOI: 10.12681/ijltic.20281
|View full text |Cite
|
Sign up to set email alerts
|

Spilling the Beans on Understanding English Idioms Using Multimodality: An Idiom Acquisition Technique for Iranian Language Learners

Abstract: Idioms are ubiquitous in English language. Despite their ubiquity, learning idioms is a thorny issue for second language learners. Multiple researchers have scrutinized different aspects of idiom learning by second language learners: important factors in processing idioms in L2 (Cieślicka, 2015); the incorporation of technology in idiom learning (Khoshnevisan, 2018b); idiom assessment (Khoshnevisan, 2018a). A number of studies have been conducted concerning the application of the Idiom Diffusion Model—an L2 id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…e bus transmission module and integrated control module of oral English automatic evaluation method are designed by using ZigBee network and IPv6 network [29]. e SCSI bus transmission control of oral English automatic evaluation method is realized by booting from external Serial EEPROM.…”
Section: Automatic Evaluation Of Spoken Englishmentioning
confidence: 99%
“…e bus transmission module and integrated control module of oral English automatic evaluation method are designed by using ZigBee network and IPv6 network [29]. e SCSI bus transmission control of oral English automatic evaluation method is realized by booting from external Serial EEPROM.…”
Section: Automatic Evaluation Of Spoken Englishmentioning
confidence: 99%
“…Consistent with Kozma, Mielke (1968) stated that irrespective of the type of media used in different studies, the results lead to "no significant difference." Clark (1983)-inconsistent with recent research (Khoshnevisan, 2020a)-reported that the results of the use of technology, regardless of the type of technology harnessed, on cognitive attainment is almost always the same. He reiterated that there were multitudinous confounding variables in the technology-related studies that the results lack sufficient convincing evidence to confirm or disconfirm the findings.…”
Section: Technology In Language Educationmentioning
confidence: 66%
“…The conceptual use of idioms [13][14][15] is actually an advanced form of connotative meaning that has long been in society at first had a bound meaning. However, the process of using the idiom that has been around for a long time in society is finally considered a word or phrase that has a free meaning.…”
Section: Discussionmentioning
confidence: 99%